2006
DOI: 10.1038/sj.ki.5000216
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute renal failure after liver transplantation

Abstract: The objective of this study was to determine the risk factors of postoperative acute renal failure (ARF) in orthotopic liver transplantation (OLT). We reviewed 184 consecutive OLT. Postoperative ARF was defined as a persistent rise of 50% increase or more of the S-creatinine (S-Cr). The patients were classified as early postoperative ARF (E-ARF) (first week) and late postoperative ARF (L-ARF) (second to fourth week). Preoperative variables were age, sex, comorbidity, indication for OLT, Child-Pugh stage, unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
191
4
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(223 citation statements)
references
References 32 publications
16
191
4
9
Order By: Relevance
“…Our results are consistent with prior studies conducted in specific subgroups, ICU patients and those undergoing cardiac surgery, in finding prior kidney function to be a main risk factor for HAKI. [11,12,[14][15][16][17][19][20][21][22][23][24][30][31][32] While prior studies have found low systolic blood pressure to be a risk factor for HAKI, we are the first to report elevated pulse as a risk factor. [6,33] Prior studies have reported that low pH and low bicarbonate levels are risk factors for HAKI.…”
Section: Discussionmentioning
confidence: 63%
“…Our results are consistent with prior studies conducted in specific subgroups, ICU patients and those undergoing cardiac surgery, in finding prior kidney function to be a main risk factor for HAKI. [11,12,[14][15][16][17][19][20][21][22][23][24][30][31][32] While prior studies have found low systolic blood pressure to be a risk factor for HAKI, we are the first to report elevated pulse as a risk factor. [6,33] Prior studies have reported that low pH and low bicarbonate levels are risk factors for HAKI.…”
Section: Discussionmentioning
confidence: 63%
“…21 Moreover few studies identified risk factors for postoperative ARF in cardiac 22 and liver transplant patients, but without developing prediction rules. 8,11,13 Therefore, the aim of this study was to develop and validate a simple and readily applicable score based on preoperative parameters to predict postoperative ARF in patients scheduled for liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Reported incidences of postoperative ARF range from 1 % after major non-cardiac surgery without liver resection 3 to around 20% after cardiac surgery [4][5][6] and up to 50% after liver transplantation. [7][8][9][10][11][12][13] The comparability of postoperative ARF across different studies is difficult due to a lack of standardized definition of ARF. Only very limited data exists regarding the occurrence of ARF in patients after liver resection, as well as its impact on outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The 15,17 , preoperative decreased renal function 7,17 , hemocomponents transfusion 1,5,18 , postreperfusion syndrome 5,19 and surgical technique 1,2 have been highlighted in the most current literature. Some preoperative co-morbidity such as hypertension, obesity (i.e.…”
Section: Discussionmentioning
confidence: 99%